Clinical course of hepatitis C virus‐positive patients with decompensated liver cirrhosis in the era of direct‐acting antiviral treatment. Issue 5 (9th March 2021) - Maesaka, Kazuki; Sakamori, Ryotaro; Yamada, Ryoko; Tahata, Yuki; Oshita, Masahide; Hagiwara, Hideki; Sakakibara, Mitsuru; Tamura, Shinji; Hiramatsu, Naoki; Inada, Masami; Iio, Sadaharu; Ito, Toshifumi; et al.
Abstract: Aim: The aim of the present study was to investigate the clinical course in hepatitis C virus (HCV)‐positive patients with decompensated liver cirrhosis after direct‐acting antivirals (DAAs) have been used for HCV infection. Methods: This multicenter study prospectively analyzed a registered cohort composed of 73 HCV‐positive patients with decompensated cirrhosis who attended our 11 institutions between January 2018 and July 2018. Prognoses, including changes in the liver reserve, hepatocellular carcinoma (HCC), decompensation events, and survival, were analyzed up to July 2020, as was the initiation of DAA treatment. Results: Sixty‐four (87.7%) and nine (12.3%) patients had Child–Pugh class (C‐P) B and C at baseline, respectively. Within 2 years after enrollment, 17 patients (23.3%) received treatment with DAAs, and 31 patients (42.5%) developed uncontrolled HCC, switched to palliative care, or died. Patients who received DAA treatment were significantly younger and had significantly higher alanine aminotransferase levels and lower platelet counts than the patients who did not receive DAA treatment. The rates of overall survival, cumulative HCC occurrence, and cumulative hospitalization for any hepatic decompensation event at 2 years were 64.8%, 13.1%, and 65.6%, respectively. Overall survival was significantly shorter and the HCC occurrence and hospitalization rates were significantly higher in C‐P C patients than in C‐P B patients. Conclusions: Among HCV‐positive patients with decompensated cirrhosis, approximately one‐fourth received DAA treatment, but more than 40% of the patients lost the opportunity for treatment with DAAs.